Queenan's Management of High-Risk Pregnancy : an Evidence-Based Approach - Queenan, John T.; Spong, Catherine Y.; Lockwood, Charles J. (Wiley-Blackwell, 2012)
For the maternal-fetal physician, constant vigilance throughout a pregnancy remains essential. But continuous change makes this an increasing challenge. Queenan's Management of High-Risk Pregnancy covers the full spectrum of perinatal care. Providing evidence, algorithms, and case studies, this book guides you through the tough and complex decisions needed to protect the health of both your fetal and the maternal patients. New material in the 6th edition covers contemporary issues such as, iron-deficient anemia, malaria, pregnancy in the disabled woman, placenta accrete, induction of labor, op.